Historias de vida y demografía de Physalaemus biligonigerus (Anura: Leptodactylidae) en una charca periurbana del centro de Argentina - Nicolino, Ana Maricel (2018)
Knowledge of population dynamics provides information on the recenthistory, current status, and future trends of a population. Physalaemus biligonigerus is widely distributed in theNeotropics, this anuran has a high and explosive reproductive activity, but its populations seem to be composedof young individuals. The objective of this study was to analyze the population demography of P. biligonigerusin a semipermanent pond in Río Cuarto, Córdoba, Argentina and to carry out a population projection through 30generations. The age structure was determined from the use of skeletochronology, and a static life table was latermade. Fertility and survival rates were calculated for each stage, by which a Leslie Matrix was constructed andthe population projection was performed. The projection shows oscillations in the number of individuals but inspite of this, the final tendency of the population is an increase in its size. The highest proportion of survivorsoccurs in the egg-to-larval stages and the mortality force acts intensively on the larval phase. The net reproductiverate indicates that the population of P. biligonigerus of the study pond is increasing.